Implementasi Nilai Keadilan Dan Tanggung Jawab Dalam Perspektif Islam Pada Proses Produksi Wirausaha Wanita Di Socah - Cindy Karunia Wati; Enni Endriyati; Dony Burhan Noor Hasan (CV. Ulil Albab Corp, 2024)
Basically, everything that is done has a goal, where the goal can be achieved after carrying out the activity. The aim of this research is to find out how the values of justice and responsibility are implemented in the production process of women's entrepreneurship Socah in Islam. And what obstacles do womenpreneurs Socah face in implementing the values of justice and responsibility in the production process. This research is also expected to provide the wider community with an understanding of the importance of the values of justice and responsibility in the production process. In the production process, the value of justice in Islam includes quality and halal raw materials, price determination, measurements/measures/weights of contents in packaging, transparency in products, and wages. Meanwhile, the value of responsibility includes environmental management, time management and consistency in products. This research was conducted qualitatively through case studies. Direct observation, interviews, and documentation. The research results show that some womenpreneurs in Socah have implemented the values of justice and responsibility in the production process. The obstacles faced by womenpreneurs are the difficulty of finding raw materials, lack of socialization about the values of justice and responsibility, and technical obstacles in the production process.